2021
DOI: 10.3920/bm2020.0098
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial differences in breast and prostate cancer cases from two randomised controlled trials compared to matched cancer-free controls

Abstract: Implicated in several chronic diseases, the gastrointestinal microbiome is hypothesised to influence carcinogenesis. We compared faecal microbiota of newly diagnosed treatment-naïve overweight and obese cancer patients and matched controls. Cases were enrolled in presurgical weight-loss trials for breast (NCT02224807) and prostate (NCT01886677) cancers and had a body mass index (BMI) ≥25 kg/m2. Cancer-free controls were matched 1:1 by age (±5 years), race, gender, and BMI (±5 kg/m2). All participants provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In this study, we identified the low rate of the order Lactobacillales and the high rate of the order Clostridiales observed in LD-fed mice. A recent study to compare fecal microbiota of patients with newly diagnosed treatment-naïve overweight and obese breast cancer or PCa (BMI > 25 kg/m 2 ) and matched controls showed that several bacteria within the order Clostridiales were significantly different in PCa cases compared with healthy controls [37]. In particular, Lachnospiraceae and Ruminococcaceae genera were highly abundant in patients with PCa compared with cancer-free controls [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified the low rate of the order Lactobacillales and the high rate of the order Clostridiales observed in LD-fed mice. A recent study to compare fecal microbiota of patients with newly diagnosed treatment-naïve overweight and obese breast cancer or PCa (BMI > 25 kg/m 2 ) and matched controls showed that several bacteria within the order Clostridiales were significantly different in PCa cases compared with healthy controls [37]. In particular, Lachnospiraceae and Ruminococcaceae genera were highly abundant in patients with PCa compared with cancer-free controls [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study to compare fecal microbiota of patients with newly diagnosed treatment-naïve overweight and obese breast cancer or PCa (BMI > 25 kg/m 2 ) and matched controls showed that several bacteria within the order Clostridiales were significantly different in PCa cases compared with healthy controls [37]. In particular, Lachnospiraceae and Ruminococcaceae genera were highly abundant in patients with PCa compared with cancer-free controls [37]. Recently, Pernigoni et al developed two mouse models to assess the effect of commensal gut microbiota on castration-resistant PCa (CRPC) progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, it has been shown that the gut microbiota is associated with the development of hepatocellular carcinoma [24] . Different features of the gut microbiota have been observed between prostate cancer patients and benign prostatic hypertrophy, while the former has presented a higher prevalence of Bacteroides massiliensis compared to cases of benign prostatic hypertrophy [25] . Furthermore, the fecal microbiota of breast cancer and prostate cancer patients differs from that of control individuals [26] .…”
Section: Gut-cancer Axis In Carcinogenesismentioning
confidence: 99%
“…Smith included the fecal microflora of 22 patients with overweight breast cancer or PCa (BMI > 25 kg/m2) and 22 controls. It was found that the β-diversity index of PCa was significantly different from that of the control group, and the abundance of Tissierellaceae , Lachnospira , and Ruminococcaceae was higher ( 29 ).…”
Section: Introductionmentioning
confidence: 96%